Research on Rural e-commerce Development under the Background of Rural Revitalization — Take Daji Town of Cao County as an Example - Zhu, Meng (Journal of Global Economy, Business and Finance, 2024)
Rural revitalization has always been an important proposition of The Times. In the context of rural revitalization, the traditional sales methods have also taken a new turn, and the shopping form of "Internet + sales" is gradually accepted by the public. Rural society has also been exposed to the Internet, and has quietly changed the new sales mode. Some rural areas have combined local resources with the Internet, expanded product sales channels, and increased economic income through e-commerce. Thanks to the development of e-commerce, many poor villages have gradually been lifted out of poverty and embarked on the road of prosperity. Now it has become a wealthy Taobao town. Daji Town, Caoxian County, Heze City, Shandong Province, is such a typical village for Internet sales. Through the analysis of rural e-commerce in Daji town, this paper puts forward relevant suggestions for the existing problems of rural e-commerce in Daji town.